36 Monocyte Subpopulations Counts and Associations with Global Longitudinal Strain in St-Elevation Myocardial Infarction Patients with Normal Ejection Fraction. (31st May 2014) - Ghattas, Angie; Shantsila, Eduard; Griffiths, Helen; Lip, G
Abstract : Introduction: Monocytes, with 3 different subsets, are implicated in the initiation and progression of the atherosclerotic plaque contributing to plaque instability and rupture. Mon1 are the "classical" monocytes with inflammatory action, whilst Mon3 are considered reparative with fibroblast deposition ability. The function of the newly described Mon2 subset is yet to be fully described. In PCI era, fewer patients have globally reduced left ventricular ejection fraction post infarction, hence the importance of studying regional wall motion abnormalities and deformation at segmental levels using longitudinal strain. Little is known of the role for the 3 monocyte subpopulations in determining global strain in ST elevation myocardial infarction patients (STEMI). Methodology: STEMI patients (n = 101, mean age 64 ± 13 years; 69% male) treated with percutaneous revascularisation were recruited within 24 h post-infarction. Peripheral blood monocyte subpopulations were enumerated and characterised using flow cytometry after staining for CD14, CD16 and CCR2. Phenotypically, monocyte subpopulations are defined as: CD14 + +CD16-CCR2+ (Mon1), CD14 + +CD16 + CCR2+ (Mon2) and CD14 + CD16 + +CCR2- (Mon3). Phagocytic activity of monocytes was measured using flow cytometry and Ecoli commercial kit. Transthoracic 2D echocardiography was performed within 7 days and at 6 months post infarct to assess global longitudinal strain (GLS) via speckle tracking. MACE was defined as recurrent acute coronary syndrome and death. Results: STEMI patients with EF ≥50% by Simpson's biplane (n = 52) had GLS assessed. Using multivariate regression analysis higher counts of Mon1 and Mon 2 and phagocytic activity of Mon2 were significantly associated with GLS (after adjusting for age, time to hospital presentation, and peak troponin levels) (Table 1 ). At 6 months, the convalescent GLS remained associated with higher counts of Mon1, Mon 2. At one year follow up, using multivariate Cox regression analysis, Mon1 and Mon2 counts were an independent predictor of MACE in patients with a reduced GLS (n = 21) (Table 2 ). Conclusion: In patients with normal or mildly impaired EF post infarction, higher counts of Mon1 and Mon2 are correlated with GLS within 7 days and at 6 months of remodelling post infarction. Adverse clinical outcomes in patients with reduced convalescent GLS were predicted with Mon1 and Mon2 suggestive of an inflammatory role for the newly identified Mon2 subpopulation. These results imply an important role for monocytes in myocardial healing when assessed by subclinical ventricular function indices.